Strategies of ICT-Based Learning Management to Improve Learning Effectiveness in SD Negeri 19 Palembang (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study explores the implementation strategies of Information and Communication Technology (ICT)-based learning management at State Elementary School 19 Palembang. The research aims to analyze how planning, organizing, implementation, and evaluation of ICT-based learning contribute to improving learning effectiveness in primary education. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving school principals, teachers, and students. The findings reveal that ICT integration was strategically planned through digital infrastructure development, teacher capacity-building programs, and the adoption of interactive learning applications. The implementation phase combined traditional and digital learning methods to enhance student engagement and motivation. Despite limited teacher competence and inadequate technical support, the school demonstrated adaptive management and collaborative problem-solving. The study underscores that effective ICT-based learning management fosters innovation, supports the development of digital pedagogy, and promotes active learning environments in elementary schools. This research provides a practical model for school leaders and policymakers to strengthen digital transformation in education, particularly in resource-constrained contexts